Smart Rings: The Future of Sleep Quality Assessment in Digital Health and AI - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Smart Rings: The Future of Sleep Quality Assessment in Digital Health and AI The pursuit of objective, continuous, and ecologically valid sleep data is ...
Keywords: Digital Health; Diagnostics; Healthcare Innovation; Machine Learning; Wearable Technology